ANALISIS PENENTUAN HARGA POKOK TARIF IKLAN PADA LEMBAGA PENYIARAN RADIO VOLARE - B1032131057, Bella Febrianty Putry (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Activity Based Costing method is a method that is significant to every activity. Activity Based Costing requires two parameters, namely: (1) The activity of each ad creation (2) the time required in the manufacture of advertising (3) the cost per minute to any overhead to be charged into the activities of manufacture or production of advertising per month This study aims to determine the type of ads on Radio Volare, the ad creation process, the unit time estimate for each activity ad creation and then allocating the cost of the ad creation by Activity Based Costing to determine the cost of advertising rates. To answer the purposes of this study, the researchers conducted a case study, by way of documentary, interview and observation. From the research conducted, researchers get the following results; unit time cost per minute in any overhead costs starting from electricity costs, fees Telephone, cost taps, Broadcast Provider License fees, charges and fees User Rights Retribution Frequency Interference (Ho). In addition, researchers can determine the estimated time within one month of advertising production, in order to know the rate per activity. Then, the researchers were also able to allocate these costs to calculate the operating costs per advertisement that can be compared with existing ad rates to see the company will have a profit or not. Keywords: ABC, Cost, Ad Rates, Radio Volare, Total Cost, Prime Time, Reguler Time